Kajian Organologi Genderang Sisibah Buatan Bapak Atur Pandapotan Solin - Rodo Andreas Panjaitan; Heristina Dewi; Yoe Anto Ginting; Rithaony Hutajulu; Hubari Gulo (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
This study describes the technique of making the traditional musical instrument Sisibah Drum preserved by Mr. Atur Pandapotan Solin at the Ninanola Studio, Sukaramai Village, Pakpak Bharat Regency. Sisibah Drum is a traditional musical instrument originating from the Pakpak tribe. This musical instrument is classified as a struck membranophone (a musical instrument whose sound source comes from skin or membrane that is played by being hit). Sisibah Drum has spiritual value and social function in carrying out traditional ceremonies such as Kerja Mbaik and Kerja Njahat. This study aims to examine and describe in depth the process of making Sisibah Drum, including its physical structure, materials and tools used, and the role of this music in the cultural life of the Pakpak people. The method used is a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews, and visual documentation. The theoretical framework includes the organological theory of Sushumu Kashima to examine the physical and structural aspects of the instrument, the Sachs-Hornbostel classification used in classifying instrument types, and the theory of musical function according to A.P. Merriam. The results of this study indicate that the Sisibah Drum is still made using traditional methods and techniques that are still used today. Local materials used in the Sisibah Drum making process consist of several types, such as Mbrabas wood, coffee wood, and animal skin. The stages used start from material selection, forming the instrument body, installing the membrane, and tuning the sound. In addition to being a musical instrument, the Sisibah Drum also functions as a means of spiritual communication and a symbol of the Pakpak tribe's cultural identity. The Ninanola Studio plays an active role in preserving the Sisibah Drum musical instrument to this day.